PEMBERDAYAAN KARANG TARUNA “BIMANTARA” DAN IBU-IBU PKK KALIKEPITING JAYA VI KELURAHAN PACAR KEMBANG, KECAMATAN TAMBAKSARI, SURABAYA DALAM MENCEGAH PENULARAN COVID-19 - Heny Arwati; Sri Wijayanti Sulistyawati; Lynda Rossyanti (Universitas Airlangga, 2021)
The community service activity was carried out with the partner of Karang Taruna Bimantara, as a youth organization located in kampung Kalikepiting Jaya VI, RT 5, RW 5, Kelurahan Pacarkembang, Kecamatan Tambaksari, Surabaya City. This activity was aimed at reviving this organization which has been inactive for a long time and empowering the youths in preventing the transmission of Covid-19. The activities offered were providing enlightenment about Covid-19, assistance in producing liquid soap, hand sanitizers and non-medical cloth masks which could be developed into productive economic businesses. The implementation of these activities also involved the organization of Family Welfare Education (Pendidikan Kesejahteraan Keluarga or PKK) which was an organization of mothers in this kampung. The enlightenment were included Covid-19 and diseases transmitted by mosquitoes, their prevention and transmission. By producing the items than can be used to prevent transmission of Covid-19 followed by obedience to the health protocols, they could participate in preventing the transmission of Covid-19. In order to increase their knowledge on productive economy, the enlightenment on productive economy, marketing of goods and financial management of business, the enlightenment was also given. Hopefully the activities which can be developed into a productive economy business can increase the income of this kampung. The enlightenment provided pre-test and post-test. Comparison of both tests resulted in an insignificant increased in knowledge on both topics. More participants and more questions are recommended to improve the more significant scores of tests. The sales of liquid soap and hand sanitizer resulted in profit can be used to reproduce. Furthermore, more assistance is needed to develop a business into a productive economy.abstrakKegiatan pengabdian masyarakat ini dilaksanakan bersama mitra Karang Taruna Bimantara yang berada di kampung Kalikepiting Jaya VI, RT 5, RW 5, Kelurahan Pacarkembang, Kecamatan Tambaksari, Kota Surabaya. Kegiatan ini bertujuan untuk menghidupkan kembali organisasi yang sudah lama tidak aktif ini dan memberdayakan para pemuda dalam rangka pencegahan penularan Covid-19. Kegiatan yang ditawarkan antara lain adalah penyuluhan tentang Covid-19, bantuan pembuatan sabun cair, hand sanitizer dan masker kain non medis yang dapat dikembangkan menjadi usaha ekonomi produktif. Pelaksanaan kegiatan ini juga melibatkan ibu-ibu yang tergabung dalam organisasi PKK (Pendidikan Kesejahteraan Keluarga) yang merupakan wadah ibu-ibu di kampung ini. Penyuluhan yang diberikan adalah mengenai Covid-19 dan penyakit yang ditularkan oleh nyamuk, pencegahan dan penularannya. Dengan memproduksi barang-barang yang dapat digunakan untuk mencegah penularan Covid-19 diikuti dengan ketaatan terhadap protokol kesehatan, mereka dapat berpartisipasi dalam mencegah penularan Covid-19. Untuk menambah pengetahuan mengenai ekonomi produktif juga diberikan penyuluhan mengenai ekonomi produktif, pemasaran barang dan cara pengelolaan keuangan hasil usaha. Diharapkan dengan adanya kegiatan yang dapat dikembangkan menjadi usaha ekonomi produktif ini dapat meningkatkan pendapatan RT setempat. Dalam penyuluhan diberikan pre-test dan post-test. Perbandingan kedua tes menghasilkan peningkatan pengetahuan yang tidak signifikan pada kedua topik tersebut. Untuk meningkatkan nilai tes yang lebih signifikan, maka diperlukan jumlah peserta dan pertanyaan yang lebih banyak. Penjualan sabun cair dan hand sanitizer menghasilkan keuntungan yang dapat dimanfaatkan untuk memproduksi lagi. Pendampingan dibutuhkan untuk mengembangkan usaha ini menjadi ekonomi produktif.